(untitled) (AYUSHDHARA, 2024)
Allergic Rhinitis becomes very common problem in now days. Patient who suffers with this aliment has symptoms like stuffy nose, continuous sneezing, red itchy and watery eyes and swelling around the eyes. All these symptoms are very much similar to Vataja pratishyaya which is a type of Pratishyaya in Ayurvedic texts. This problem become serious when it hamper the patient daily routine. Allopathic medicine only gives symptomatic relief. Ancient science Ayurveda always focus on the route cause so that we can find an effective treatment plan. To find the root cause of disease it is very necessary to do the Panchnidanatmak study of Vataja Pratishyaya.